Lycium barbarum glycopeptide mitigates retinal ischemia-reperfusion injury through its anti-inflammatory, anti- senescence, and anti-apoptosis properties - Chunlin Zhao; Xuejing Lu; Yanxia Zhao; Wei Shi (Scientific Reports)
Abstract This study investigates the therapeutic potential of lycium barbarum glycopeptide (LbGp) in mitigating retinal ischemia-reperfusion injury (RIRI), a key pathological mechanism in glaucoma. RIRI involves inflammation, cellular senescence, and apoptosis, leading to retinal ganglion cell (RGC) degeneration and optic nerve damage. Using in vivo and in vitro models, the study evaluated LbGp’s anti-inflammatory, anti-senescence, and anti-apoptotic properties. In vivo, RIRI was induced in C57BL/6J mice by elevating intraocular pressure, followed by reperfusion, with LbGp administered orally. In vitro, R28 cells underwent oxygen-glucose deprivation/reoxygenation (OGD/R) to simulate RIRI, with LbGp added to cultures. Retinal structure and function were assessed using optical coherence tomography (OCT), OCT angiography (OCTA), and hematoxylin-eosin (HE) staining, while inflammatory markers (IL-6, IL-1β, TNFα), senescence markers (p21, p16), and apoptosis were evaluated via immunofluorescence, enzyme linked immunosorbent assay (ELISA), senescence-associated β-galactosidase (SA-β-gal) staining, terminal dUTP Nick End Labeling (TUNEL) assays, and flow cytometry (FCM). Results showed LbGp restored retinal blood flow, reduced retinal thinning, and improved RGC survival, while decreasing inflammatory, senescence and apoptosis markers. These findings suggest LbGp is a promising therapeutic candidate for glaucoma and ischemic retinal conditions, warranting further research to elucidate its mechanisms and clinical efficacy.